2022
DOI: 10.3390/ijms231810361
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Ghrelin, Glucagon, Visfatin and Glp-1 Are Decreased in the Peritoneal Fluid of Women with Endometriosis along with the Increased Expression of the CD10 Protease by the Macrophages

Abstract: The aim of this study was to evaluate the levels of ten energy metabolism factors: C-peptide, ghrelin, GIP, GLP-1, glucagon, insulin, leptin, PAI-1 (total), resistin, and visfatin, and to determine the expression of GLP1R receptors, CD10, CD26 proteases, and pro-inflammatory marker CD86 by macrophages in the peritoneal fluid (PF) in patients with endometriosis. The study included 54 women with endometriosis and a control group of 30 women with uterine myoma without signs of endometriosis. The levels of factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Pretreatment with 16α-OHE1 minimized CD68-positive cell in ltration. The phenotypic ratio was evaluated by CD86 and CD206 immunostaining, and most CD68-positive cells that in ltrated the myocardium during hypoxia were CD86-positive cells, while CD206positive cells were less abundant, indicating in ammatory in ltration of the rat myocardium [36,37] .…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with 16α-OHE1 minimized CD68-positive cell in ltration. The phenotypic ratio was evaluated by CD86 and CD206 immunostaining, and most CD68-positive cells that in ltrated the myocardium during hypoxia were CD86-positive cells, while CD206positive cells were less abundant, indicating in ammatory in ltration of the rat myocardium [36,37] .…”
Section: Discussionmentioning
confidence: 99%
“…CCL13 belongs to the CC chemokine family and is involved in CCR2 and CCR3 , the migration of monocytes/macrophages, T-lymphocytes, and eosinophils via its functional ligands ( 37 ). CD86 , a pro-inflammatory indicator for peritoneal macrophages, plays a crucial role in anti-endometriosis ( 38 ). CSF-1 is released by endometriotic macrophages and is involved in the formation of early endometriotic lesions through the enhancement of cell proliferation as well as via the attachment and invasion of endometrial cells ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, accumulating evidence suggests that the local immune microenvironment may play a key role in the onset, development, and progression of endometriosis [ 6 ]. In this context, Krasnyi and coworkers found that the concentrations of ghrelin, GLP-1, glucagon, and visfatin in the peritoneal fluid were reduced in women with endometriosis [ 7 ]; at the same time, they noted an increase in CD10 protease expression by peritoneal macrophages, with a positive correlation of ghrelin and GLP-1 levels with CD86 macrophage expression in the study group; finally, a positive correlation was also found between the levels of GLP-1, glucagon, and visfatin with CD26 macrophage expression in peritoneal fluid, confirming the clear role of macrophages in the development of endometriosis [ 8 ]. From another perspective, Suszczyk et al found an elevated percentage of myeloid dendritic cells and plasmacytoid dendritic cells with PD-L1 or PD-L2 expression and a higher concentration of the soluble forms of PD-L1 and PD-L2 in the peritoneal fluid than in the plasma of endometriosis patients [ 9 ], suggesting potential pathways to be elucidated for the onset of cancers from atypical endometriosis [ 10 ].…”
mentioning
confidence: 99%